Implementasi Kebijakan Pembentukan Daerah Otonom Baru dan Dampaknya Bagi Kualitas Pelayanan Publik - Daud M Liando (Magister Ilmu Administrasi Publik, 2012)
The purpose of the policy is the establishment of new autonomous regions to facilitate the implementation of quality public services. The emergence of a new autonomous region is expected to improve the way local government more effective. This study reveals the impact of the establishment of few autonomous regions, South Minahasa regency on the quality of public services, particularly the population of administrative services. Implementations of the policy formation of autonomous regions have an impact on the quality of administrative service population. Some of the factors the lead to less than optimal public service facilities and infrastructure are less adequate human resources that have not worked in a professional, institutional aspects are still too weak aspects of the limited budget. On the community side, the lack of awareness of the importance of ID cards and the lack of public knowledge makes people participate less in performance improvement of administrative services population.